Horticultural Therapy: An Ancient Technique in a Modern World - Gary Altman; Nrupali Patel (Dr. Chinmay Pandya, 2021)
Horticultural therapy utilizes plants and plant-based activities in the treatment and rehabilitation of individuals with various disabilities.  The practice has been in use since the time of ancient Egypt, Hindus and other cultures. In the United States, The American Horticultural Therapy Association is the professional society that has established educational and training standards for those wishing to practice in the profession of horticultural therapy. Various studies have shown the positive mental and physiological healing benefits of plant-based activities.  While horticultural therapy has not achieved the evidence-based practice standard on its own, this treatment approach is flexible and adaptable enough to be integrated into existing scientific evidence-based therapy practices in mental healthcare. Despite current challenges with horticultural therapy practice, the use of plants and plant-based activity as a therapeutic method will continue to have a role in the healthcare community. Plants and gardening activity are benign and non-threatening, making their use in therapeutic treatments an appealing approach to populations worldwide.